Pregnancy after abdominoplasty with mesh placement: A case report. (December 2020) - Faessen, Jelle L.; Meesters-Caberg, Marleen A.J.; Stoot, Jan H.M.B.
Summary: A 32-year-old Caucasian female, who had an abdominoplasty with sublay mesh placement for rectus abdominis diastasis becamepregnant one year later. The gestation was uneventful and the baby was born healthy after 40 weeks of pregnancy. During and after the pregnancy the patient's abdomen had been evaluated intensively and there was no recurrence of rectus abdominis diastasis. In this particular case the tissues of the abdominal wall elongated as the foetus grew larger, except for the site where the rectus diastasis has been corrected. The experience with this particular case does not assure that all patients will have the same uneventful outcomes as described. Nonetheless, it shows that pregnancy after abdominoplasty with mesh placing for rectus abdominis diastasis can be safe for both mother and child. However, each patient must be informed about the risks of pregnancy in this particular situation and professional follow-up is mandatory when pregnancy does occur. This is, as far as we know, the first case report of an uneventful pregnancy after rectus abdominis diastasis repair with the placement of a sublay mesh and abdominoplasty.